Revisiting the educational heritage of India - Singh, Sahana (New Delhi Vitasta, 2022)
Long before the first European universities appeared, India already had multi-disciplinary centres of learning that fuelled a knowledge revolution around the world. This book fills a dire need to chronicle the great educational heritage of India. It describes a unique ecosystem which ensured that Gurus and Acharyas handed the lamp of learning to generations of students. As the author puts it, (3z(BWhen swords quenched their thirst and famine ravaged the lands, Indians still held on to their truth that there was nothing more purifying than knowledge.(3y (BShe has collated information from oral history, local lore, travelogues, surviving literature, inscriptions, salvaged manuscripts and accounts of scholars and laity. Historically, the book covers a vast time span from ancient India$1 (Bs traditions to the deliberate destruction of its heritage. It also outlines steps that can be taken today to incorporate the most relevant aspects of ancient learning systems into the current structure of school and university education.s